PENGARUH MEDIA PEMBELAJARAN TEKNOLOGI INFORMATIKA KOMPUTER DAN PENGGUNAAN MESIN KASIR TERHADAP PRESTASI BELAJAR PENGELOLAAN USAHA PEMASARAN SISWA KELAS X JURUSAN PEMASARAN SMKN 1 KOTA PROBOLINGGO - Purwanti Purwanti (Jurnal Penelitian dan Pendidikan IPS, 2016)
This research aims to know the influence of instructional media of computer information technology to learning achievement of marketing business management, the influence of using cash register to learning achievement of marketing business management, and the influence of instructional media of computer information technology and the use of cash register influence together to learning achievement of ten grader marketing students SMKN 1 Probolinggo. Eighty (80) students are involved as the respondents. Further, the results show that the use of instructional media of computer information technology and cash register influence significantly to learning achievement of marketing business management and the use of both together influence significantly to learning achievement of ten grader marketing students SMKN 1 Probolinggo.